Does Firm Size, Leverage, and Gender Diversity Affect Intellectual Capital Disclosure? - Suzan, Leny; Nurhakim, Qoyyimah (UNIVERSITAS PAKUAN, 2023)
This study pursues to find out the effect of firm size, leverage, and gender diversity on intellectual capital disclosure (ICD) by investigating 41 selected companies register on the Indonesia Stock Exchange (IDX). Utilizes the panel data method to carry out fixed effect regression with software tools, namely Eviews 12 SV, as well as using a sample of companies in the registered infrastructure, utilities, and transportation sectors to obtain relevant variables; it collects data for 2018-2020. The results reveal that partially firm size and gender diversity have influence on ICD. This validates its impact on the decision-making needs of stakeholders. At the same time, leverage has no effect on ICD. However, the three independent variables simultaneously have a significant effect on ICD. High disclosure results generate benefits to attract (prospective) investors, eliminate negative views in the market, increase employee and stakeholder trust and loyalty, and are used to obtain higher selling points to be acquired.